Tissue‐Specific Distribution and Maternal Transfer of Persistent Organic Halogenated Pollutants in Frogs - Guan, Ke‐Lan; Luo, Xiao‐Jun; Zhu, Chu‐Hong; Chen, Xi; Chen, Peng‐Peng; Guo, Jian; Hu, Ke‐Qi; Zeng, Yan‐Hong; Mai, Bi‐Xian (Environmental toxicology and chemistry, 2024)
Abstract Persistent organic pollutants pose a great threat to amphibian populations, but information on the bioaccumulation of contaminants in amphibians remains scarce. To examine the tissue distribution and maternal transfer of organic halogenated pollutants (OHPs) in frogs, seven types of tissues from black‐spotted frog (muscle, liver, kidney, stomach, intestine, heart, and egg) were collected from an e‐waste–polluted area in South China. Among the seven frog tissues, median total OHP concentrations of 2.3 to 9.7 μg/g lipid weight were found (in 31 polychlorinated biphenyl [PCB] individuals and 15 polybrominated diphenyl ether [PBDE], dechlorane plus [syn‐DP and anti‐DP], bexabromobenzene [HBB], polybrominated biphenyl] PBB153 and ‐209], and decabromodiphenyl ethane [DBDPE] individuals). Sex‐specific differences in contaminant concentration and compound compositions were observed among the frog tissues, and eggs had a significantly higher contaminant burden on the whole body of female frogs. In addition, a significant sex difference in the concentration ratios of other tissues to the liver was observed in most tissues except for muscle. These results suggest that egg production may involve the mobilization of other maternal tissues besides muscle, which resulted in the sex‐specific distribution. Different parental tissues had similar maternal transfer mechanisms; factors other than lipophilicity (e.g., molecular size and proteinophilic characteristics) could influence the maternal transfer of OHPs in frogs. Environ Toxicol Chem 2024;43:1557–1568. © 2024 SETAC